Mark: a reader-response commentary - Iersel, Bastiaan Martinus Franciscus van (Journal for the study of the New Testament / Supplement series, 1998)
The distinguished Dutch New Testament scholar Bas van Iersel offers us an incisive and comprehensive episode-by-episode commentary on the Gospel of Mark. His special focus is on the contribution of each episode to the overall meaning of the gospel, at both the level of the story and the level of the discourse. As a reader-response commentator, his concern is everywhere with the effect of Mark's story on its readers, engaging both with the situation of the original audience of Mark-Christians of Gentile origin in Rome shortly after the Neronian persecutions-and with that of the present-day reader. Even the introductions are reader-related: on the role of the reader, the original audience and the reader of today, the overall concentric structure of Mark, and the relation of Mark to the Old Testament.